Pengaruh Jarak Tanam dan Jumlah Benih Per Lubang Tanam terhadap Pertumbuhan dan Hasil Jagung (Zea Mays L.Var. Sele) - Delfim da Costa; Salensia Haryati Afonso; Agapito Cardoso; Oktaviana Rosario Sere Gili (Agriculture - Jurnal Ilmu Pertanian, 2026)
The study aimed to define proper plant spacing and the number of seeds per planting hole to improve the yield of the maize variety Sele. The maize variety Sele is one of the recommended varieties in Timor-Leste and has been planted across the country for more than 2 decades. The study was conducted in Hera-Acanuno, Dili, Timor-Leste, from August to November 2025. The experimental design was arranged according to the randomized block design factorial 3x3 in 3 blocks. The first factor consists of 3 levels of treatments: D1 = 75 cm x 40 cm, D2 = 75 cm x 50 cm, and D3 = 75 cm x 60 cm. The second factor consists of 3 levels of treatments: NM1 = one seed per planting hole, NM2 = two seeds per planting hole, and NM3 = three seeds per planting, resulting in 9 units of combination treatments that were repeated in three blocks to have 27 units of treatments. Environmental variables were observed three times at the beginning, middle, and end of the study period. The vegetative variables were measured repeatedly every 3 weeks, followed by the generative variables at the harvesting period. The result of the study indicated no interaction between these two factors; however, plant spacing and number of seeds significantly influence the environment and vegetative and generative variables. The planting distance of 70 cm x 40 cm had the higher yield (6.15 t/ha), and the planting distance of 70 cm x 60 cm had the lower yield (4.91 t/ha). In addition, the number of seeds per planting hole indicated that one seed per hole yielded 7.64 t/ha, while three seeds per planting hole gave 3.20 t/ha. Thus, this study recommended adopting a narrow planting distance of 70 cm x 40 cm with one seed per planting hole.